Jesus and the manuscripts what we can learn from the oldest texts - Evans, Craig A. 1952- (Hendrickson Academic, 2020)
"Jesus and the Manuscripts, by popular author and Bible scholar Craig A. Evans, introduces readers to the diversity and complexity of the ancient literature that records the words and deeds of Jesus. This diverse literature includes the familiar Gospels of the New Testament, the much less familiar literature of the Rabbis and of the Qur’ān, and the extracanonical narratives and brief snippets of material found in fragments and inscriptions. This book critically analyzes important texts and quotations in their original languages and engages the current scholarly discussion. Evans argues that the Gospel of Thomas is not early or independent of the New Testament Gospels but that it should be dated to the late second century. He also argues that Secret Mark, like the recently published Gospel of Jesus’ Wife, is probably a modern forgery. Of special interest is the question of how long the autographs of New Testament writings remained in circulation. Evans argues that the evidence suggests that most of these autographs remained available for copying and study for more than one hundred years and thus stabilized the text." -- from publisher's website
Hier auch später erschienene, unveränderte Nachdrucke ; Verfasser des Vorworts aus dem Inhalt entnommen, auf dem Schutzumschlag enthalten
Keywords: Jesus Christus; Geschichtlichkeit; Quelle; Jesus Christ / Historicity; Bible / New Testament / Manuscripts; Bible / New Testament / Criticism, interpretation, etc; Bible / Gospels / Arabic / Versions; Rabbinical literature / Relation to the New Testament; Apocryphal books (New Testament); Jesus Christ; Bible / Gospels; Bible / New Testament; Historicity of Jesus Christ; Criticism, interpretation, etc; Manuscripts